Assosiation Of Metabolic Syndrome And Female Pattern Hair Loss (Latakia University Journal -Medical Sciences Series, 2024)
Background: Female pattern hair loss may be associated with several disease such as high blood pressure ,hyperandrogenism and  pcos and these women may have high cholesterol  levels and increased  risk of  late onset of diabetes.Aim:.this study aims to investigate the relationship between FPHL and the chronic metabolic abnormalitis (Metabolic syndrome diagnosed according to the Adult Treatment Panel-III criteria)Materials and Methods: This study was conducted in the department of dermatology, Tishreen university, Lattakia, Syria. The study included 50 patients and 50 controls, matched in age and sex. Abdominal circumference (WC) and blood pressure(SBP,DBP) were measured. Fasting serum concentration  was measured for each of FBG, HDL, TG. Results: Metabolic syndrome was diagnosed in 15 patients with FPHL(30%)  compared with 6 control subjects(12%) (P= 0.031).The most common feature in the patients was an increased: waist circumference in patients compared with control (50% compared with 26% pvalue